2006
DOI: 10.1111/j.1574-6941.2006.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and biogeography of haloalkaliphilic sulphur-oxidizing bacteria belonging to the genus Thioalkalivibrio

Abstract: A group of 85 isolates of haloalkaliphilic obligately chemolithoautotrophic sulphur-oxidizing bacteria belonging to the genus Thioalkalivibrio were recently obtained from soda lakes in Mongolia, Kenya, California, Egypt and Siberia. They have been analyzed by repetitive extragenic palindromic (rep)-PCR genomic fingerprinting technique with BOX- and (GTG)5-primer set. Cluster analysis was performed using combined fingerprint profiles and a dendrogram similarity value (r) of 0.8 was used to define the same genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
3
34
0
2
Order By: Relevance
“…The finding that geographic distance affects bacterial biogeography is consistent with the other studies (e.g., references 12, 22, and 51) and has been explained by the fact that, at a long geographic distance, barriers to dispersal are more likely, and so evolutionary events such as speciation and extinction can give rise to differences in two populations separated by such barriers (32). Our finding is consistent with previous studies on Thioalkalivibrio and Salinibacter ruber, which showed that strains of both bacterial species were endemic to certain regions, despite having cosmopolitan distributions (22,58).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The finding that geographic distance affects bacterial biogeography is consistent with the other studies (e.g., references 12, 22, and 51) and has been explained by the fact that, at a long geographic distance, barriers to dispersal are more likely, and so evolutionary events such as speciation and extinction can give rise to differences in two populations separated by such barriers (32). Our finding is consistent with previous studies on Thioalkalivibrio and Salinibacter ruber, which showed that strains of both bacterial species were endemic to certain regions, despite having cosmopolitan distributions (22,58).…”
Section: Discussionsupporting
confidence: 83%
“…However, due to the small number of studies available thus far, this conclusion should be treated with caution. For example, studies at large-scale distances have been carried out on prokaryotes inhabiting extreme environments, in which the environmental parameters have a relatively small range, and focus on a particular prokaryotic species (22,51,63), while studies at small-scale distances target mixed bacterial populations (14). It is possible that this trend has arisen from the types of habitats sampled or the organism studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the multiple extreme conditions (pH, alkalinity-salinity, increased irradiation and, sometimes, temperature) in the saline and alkaline lakes, the (micro) diversity of SOB is remarkably high (Foti et al 2006;Sorokin et al 2006b). In the present paper we describe the isolation of a facultatively alkaliphilic and halophilic chemolithoautotrophic sulfur-oxidizing bacterium (strain ALCO 1) from hypersaline soda lakes in S-W Siberia.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaliphiles are found in natural alkaline environments such as saline soda lakes and ponds of East Africa (Foti et al, 2006), Europe (Gerasimenko et al, 2003), Asia (Antony et al, 2013), Ca 2+ alkaline springs of Near East, and soda deserts of North America (Duckworth et al, 1996). Marine environments contain many alkalitolerant bacteria and usually a smaller number of alkaliphiles (Ntougias et al, 2006;Tamura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%